Quantification of the sensitivity increase of a micro-high-performance liquid chromatography–electrospray ionization mass spectrometry system with decreasing column diameter - Legido-Quigley, C; Smith, N.W; Mallet, D (Journal of Chromatography A, 2002)
This study details the sensitivity achieved with capillary columns when used with a micro-HPLC–electrospray ionization MS system. It is comprised of two sections, the first is the comparative study of three columns, one of narrow-bore diameter and two of capillary diameter. The second section compares three columns of decreasing diameter in the capillary scale. All the experiments achieved enhanced sensitivity using capillary columns. The increase in the experimental MS response ranged from −20% to +20% compared to the UV experimental response when decreasing the internal diameter of the columns used. When comparing the experimental MS response to the maximum theoretical UV response achievable, the increase in response ranged from 40 to 50%.